2014
DOI: 10.1007/s11357-014-9724-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-543 and miR-590-3p regulate human mesenchymal stem cell aging via direct targeting of AIMP3/p18

Abstract: A b s t r a c t P r e v i o u s l y, A I M P 3 ( a m i n o a c y ltRNAsynthetase-interacting multifunctional protein-3) was shown to be involved in the macromolecular tRNA synthetase complex or to act as a tumor suppressor. In this study, we report a novel role of AIMP3/p18 in the cellular aging of human mesenchymal stem cells (hMSCs). We found that AIMP3/p18 expression significantly increased in senescent hMSCs and in aged mouse bone marrow-derived MSCs (mBM-MSCs). AIMP3/p18 overexpression is sufficient to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Senescence-associated beta-galactosidase staining was conducted as previously described [11]. Briefly, TMSCs were seeded into 6-well plates and incubated to reach 70-80% confluency.…”
Section: Senescence-associated Beta-galactosidase Stainingmentioning
confidence: 99%
“…Senescence-associated beta-galactosidase staining was conducted as previously described [11]. Briefly, TMSCs were seeded into 6-well plates and incubated to reach 70-80% confluency.…”
Section: Senescence-associated Beta-galactosidase Stainingmentioning
confidence: 99%
“…A recent research has showed that miR-543 functions as an oncogene in hepatocellular carcinoma by targeting PAQR3 [27]. In addition, miR-543 has also been found to decrease the tumor suppressor AIMP3 in human stem cell by targeting AIMP3/p18 [28]. However, the biological effect of miR-543 in prostate cancer and the correlation between miR-543 and RKIP have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…They also mediate several crucial signaling pathways in inflammation and carcinogenesis [8,10,11]. The role of NF-κB-related miRNA has been established in cancer, stem cells and lipid accumulation, but not in inflammation [12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%